1990
DOI: 10.1021/jm00172a036
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and activity of a potent N-methyl-D-aspartic acid agonist, trans-1-aminocyclobutane-1,3-dicarboxylic acid, and related phosphonic and carboxylic acids

Abstract: We report the synthesis of a series of 3-carboxy-, 3-(carboxymethyl)-, 3-(omega-phosphonoalkyl)-1-aminocyclobutane-1-carboxylic acids for evaluation as agonists or antagonists of neurotransmission at excitatory amino acid receptors, particularly N-methyl-D-aspartic acid (NMDA) receptors. The compounds were evaluated as agonists on their ability to depolarize the rat brain cortical wedge preparation or as antagonist of the actions of the selective agonists NMDA, quisqualic acid, and kainic acid. The chain-elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 0 publications
0
52
0
Order By: Relevance
“…The combined organic extracts were washed with water, brine, dried with MgSO 4 , filtered, concentrated, and finally dried in high vacuum. 13 and (ent-5a), respectively…”
Section: -(Rsmentioning
confidence: 99%
“…The combined organic extracts were washed with water, brine, dried with MgSO 4 , filtered, concentrated, and finally dried in high vacuum. 13 and (ent-5a), respectively…”
Section: -(Rsmentioning
confidence: 99%
“…As pointed out earlier, there has been a wealth of information on the substrate specificity and structural requirements of GluT 19,26,34,[92][93][94][95][96][97][98][99][100][101]103,105,[107][108][109] even in relation to individual EAAT's 110,112,114,[179][180][181][182][183] yet this structure-activity data has not so far been satisfactorily matched with the protein architecture of the putative substrate-binding regions. Moreover, some of the EAAT's may form multimeric complexes 184) and most of them also act as chloride channels 185) ; for a review see ref.…”
Section: Unresolved Problems and Future Direc-tionsmentioning
confidence: 99%
“…It was found to have a very high affinity and specificity for GluT 105) (for a review see 13) ) and recent studies using NMR analyses have shown that L-CCG III can be very rapidly accumulated by brain slices, even against steep concentration gradients. 106) Other conformationally-restricted glutamate analogues have been synthesised and used as substrates/inhibitors of GluT [107][108][109] ; for a review see. 110) In some cases, such compounds have been shown to be transporter selective.…”
Section: H]d-aspartate Compared To the Distribution Of Glast (Eaat1) mentioning
confidence: 99%
“…For stimulation of glutamate receptors (NMDA, AMPA, Kainate and metabotropic receptor) four agonists were used, respectively: trans-1-Aminocyclobutan-1,3-dicarboxylic acid (ACBD [13], (S)-(-)-α-Amino-5-fluoro-3,4-dihydro-2,4-dioxo-1(2H)-pyrimmidinepropanoic acid (S-Fluorowillardiine [14]- [16], (RS)-2-Amino-3-(3-hydroxy-5-tert-butyliosxazol-4-yl)propanoic acid (ATPA; [17]- [20] and (±)-1-Aminocyclopentane-trans-1,3-dicarboxylic acid (t-ACPD; [21]- [23]. All agonists were tested in pilot experiments in order to detect a concentration leading to strong increases of population spike amplitude in the presence of single stimuli (SS) and theta burst stimulation (TBS).…”
Section: Hippocampal Slice Preparation In Vitromentioning
confidence: 99%